Analisis Tentang Gerakan Mahasiswa Universitas Riau - Aditya Putra Gumesa; Sri Erlinda; Zahirman Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: University of Riau students who were in the media spotlight both nationally and regionally due to the movement of students who demonstrated. Seen some of the Government's strategic buildings become places where students convey their aspirations. But the accusation is that the student movement is a practical political movement, selling idealism, and agents of certain political parties. So the author wants to analyze how the characteristics and driving factors of the University of Riau student movement. This research method is descriptive qualitative. The research instrument used was a questionnaire consisting of 31 and interviews. Data analysis techniques using the formula P = f / Nx100% to find out the percentage of answers from respondents. Based on the results of the study that the movements of the University of Riau students have the following characteristics, (1). Spontaneous, (2). Non structural pattern, (3). Not a political agent. (4). Has a wide network. (5). The student movement is under the direction of a long-term organization. (6). The student movement aims to influence and suppress government policies and make political changes, (7). The student movement is carried out with full awareness. (8). The student movement does not form official institutions such as political parties, but rather embodies the collective movement. (9). The student movement has ideology. (10). In holding a collective action the student movement displays strategic issues in the means of mass mobilizing and streamlining the action. (11). The student movement is anti-violence. While the driving factors of the Riau university student movement consist of: (1). Moving students is born by conditions that provide opportunities for the movement. (2). The student movement arises because of dissatisfaction and reaction to social, political, economic, and clogged channels of democracy. (3). Students move because there is no respect for local norms. (4). Students move because there is no longer legal independence Key Words: Movement, Students